Pengelolaan Hotel Berdasarkan Konsep Syaria (Studi Kasus Hotel Al-Badar Makassar) - Rachmat Sugeng; Edwin Basmardst (Jurnal Ilmiah Ekonomi Islam, 2021)
Hotel Al-Badar Makassar as one of the sharia business concept that was founded on the basis of several reasons. One of them is to enforce Islamic rule with sharia label. Hotel Al-Badar Makassar in running its business activities always apply the principles of sharia that support the high values of Islamic religion. This research uses descriptive qualitative method. Primary data in this research obtained through observation, interview, and literature study. While the secondary data obtained from existing sources in the form of history of research sites. The result of the research shows that Hotel Al-Badar Makassar can not be said as Shariah Hotel because it has not fulfill the standard set by Fatwa DSN-MUI Number 108/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles and the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia No. 2 of 2014 concerning Guidelines for the Implementation of Sharia Hotel Business, Criteria of Hotels sharia Hilal 1 and Criteria of Hotels Sharia Hilal 2, as required by sharia hotels in running their business.